A comparison of endovascular versus open repair for ruptured abdominal aortic aneurysm – Meta-analysis of propensity score-matched data. (August 2022) - Alsusa, Hatim; Shahid, Abbas; Antoniou, George A
Background: Optimal management of ruptured abdominal aortic aneurysms (rAAA) has been heavily debated in the literature. The aim of this review is to assess comparative outcomes from propensity-matched studies of endovascular versus open for rAAA. Methods: Electronic databases (MEDLINE and Embase) were searched in January 2021 using the Healthcare Databases Advanced Search interface. Eligible studies compared endovascular versus open repair for rAAA using propensity-matched cohorts. Pooled estimates of perioperative outcomes were calculated using odds ratio (OR) or mean difference (MD) and 95% confidence interval (CI) using the random-effects model. Time-to-event data meta-analysis was conducted using the inverse-variance method and reported as summary hazard ratio (HR) and associated 95% CI. The quality of evidence was graded using a system developed by the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) working group. Results: Six studies published between 2010 and 2020 were selected for qualitative and quantitative synthesis, reporting a total of 6731 patients. The odds of perioperative mortality after endovascular aneurysm repair (EVAR) were significantly lower than after open surgical repair (OSR) (OR 0.52, 95% CI 0.41–0.65). The hazard of overall mortality during follow-up was lower, although not significantly, after EVAR than after OSR (HR 0.79, 95% CI 0.62–1.01). The odds of acute kidney injury and early aneurysm-related reintervention were both significantly lower after EVAR than after OSR (OR 0.34, 95% CI 0.14–0.78 and OR 0.57, 95% CI 0.33–0.98, respectively). Patients treated with EVAR stayed in hospital for significantly less time than those treated with OSR (MD −5.13, 95% CI −7.94 to −2.32). The certainty of the body of evidence for perioperative mortality was low and for overall mortality was very low. Conclusion: The evidence suggests that EVAR confers a significant benefit on perioperative mortality.